2018
DOI: 10.1016/j.neuropsychologia.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Aging-associated changes of movement-related functional connectivity in the human brain

Abstract: Motor performance declines with normal aging. Previous neuroimaging work revealed aging-related general increases in neural activity, especially in the prefrontal and pre-motor areas, associated with a loss of hemispheric lateralization. However, the functional mechanisms underlying these changes and their relation to aging-associated motor decline to date remain elusive. To further elucidate the neural processes underlying aging-related motor decline, we recorded EEG from younger and older subjects while they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 53 publications
1
32
1
Order By: Relevance
“…Several studies using data from EEG/MEG/single-unit/ECog recordings while subjects performed a variety of different motor tasks showed that remote neural populations synchronize over a short-time period (Singer, 1999(Singer, , 2004Uhlhaas, Roux, Rodriguez, Rotarska-Jagiela, & Singer, 2010;van Wijk, Beek, & Daffertshofer, 2012), suggesting that coordinated timing constitutes a fundamental principle involved in motor and cognitive processing (Uhlhaas et al, 2010;Fries, 2005Fries, , 2015Baker, Olivier, & Lemon, 1997;Baker, Spinks, Jackson, & Lemon, 2001). Furthermore, we could show in a previous study (Rosjat et al, 2018) that during voluntary, i.e. internally-triggered movements, motor-related networks built on inter-regional neural synchronization in the lower frequencies in younger as well as older subjects.…”
Section: /30mentioning
confidence: 75%
See 4 more Smart Citations
“…Several studies using data from EEG/MEG/single-unit/ECog recordings while subjects performed a variety of different motor tasks showed that remote neural populations synchronize over a short-time period (Singer, 1999(Singer, , 2004Uhlhaas, Roux, Rodriguez, Rotarska-Jagiela, & Singer, 2010;van Wijk, Beek, & Daffertshofer, 2012), suggesting that coordinated timing constitutes a fundamental principle involved in motor and cognitive processing (Uhlhaas et al, 2010;Fries, 2005Fries, , 2015Baker, Olivier, & Lemon, 1997;Baker, Spinks, Jackson, & Lemon, 2001). Furthermore, we could show in a previous study (Rosjat et al, 2018) that during voluntary, i.e. internally-triggered movements, motor-related networks built on inter-regional neural synchronization in the lower frequencies in younger as well as older subjects.…”
Section: /30mentioning
confidence: 75%
“…Third, we wanted to analyze whether the neural evidence for the HAROLD model found in voluntary, i.e. self-initiated movements (Rosjat et al, 2018) could be replicated in visually-cued movements, i.e. whether the neural underpinnings are independent of the way the movement was initiated.…”
Section: /30mentioning
confidence: 99%
See 3 more Smart Citations